Comparison of three-field and four-field planning techniques in patients with localized prostate cancer - Dymnicka, Magdalena; Milecki, Piotr; Piotrowski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2003)
Purpose. To compare three-field and four-field planning techniques in patients with localized prostate cancer. Material and methods. Twenty patients (T1-T2N0M0) were chosen for the analysis of treatment plans. The following three-field and four-field plans were created: 3 field techniques with beam angles orientations; 0º, 120º, 240º and 0º, 90º, 270º, and 4 field technique (0º, 90º, 180º, 270º). One hundred and twenty treatment plans were created and compared according to the following parameters: the mean total dose (MTD), the Normal Tissue Complication Probabilities (NTCP), and the volume of OARs which received arbitrary chosen fraction (%) of the total prescribed dose (73.8 Gy=100%). All calculated parameters were statistically verified using statistical methods (ANOVA). Results. There were no significant differences in the distribution of MTD and TCP for the PTV. T technique gave the best protection of rectum. No significant differences were observed for bladder. The distribution of MTD, NTCP and V70 in the right femoral head was below the tolerance dose. Conclusions. The study has shown that the three-field technique (an anterior and two opposing lateral fields) with the following portals orientation 0º, 90º, 270º applying photons of 20 MV energy provided the greatest rectal protection without any significant differences in dose distribution in the target (PTV). To sum up, we could recommend the 3 field technique (0º, 90º, 270º) as valuable for implementation in radiotherapy of prostate cancer at the stage of T2N0M0.